2008
DOI: 10.1097/tp.0b013e318186dd0c
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Study of Tacrolimus as Secondary Intervention Versus Continuation of Cyclosporine in Renal Transplant Patients at Risk for Chronic Renal Allograft Failure

Abstract: In this study, patients with chronic allograft damage converted from cyclosporine to tacrolimus demonstrated no apparent benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Tacrolimus has been identified as a clinically and pharmacoeconomically superior calcineurin inhibitor thus a majority of new transplant recipients should receive tacrolimus [41]. Nevertheless there are no data to suggest that switching from cyclosporin to tacrolimus after stabilization has benefits on long-term outcomes so patients already stabilized on cyclosporin generally remain on it [42][43][44]. This is consistent with utilization patterns seen in this study, with cyclosporin utilization decreasing gradually over time, not dropping off completely.…”
Section: Discussionsupporting
confidence: 78%
“…Tacrolimus has been identified as a clinically and pharmacoeconomically superior calcineurin inhibitor thus a majority of new transplant recipients should receive tacrolimus [41]. Nevertheless there are no data to suggest that switching from cyclosporin to tacrolimus after stabilization has benefits on long-term outcomes so patients already stabilized on cyclosporin generally remain on it [42][43][44]. This is consistent with utilization patterns seen in this study, with cyclosporin utilization decreasing gradually over time, not dropping off completely.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, some studies have shown that conversion from ciclosporin to tac is beneficial for patients with deteriorating graft function [39], and that introduction of MMF has a similar effect [40]. Although other studies have reported contradictory results [41], much of this literature is difficult to interpret because many studies do not distinguish between CR and other causes of chronic graft dysfunction [42]. …”
Section: Discussionmentioning
confidence: 99%
“…Twoyear follow-up results were improvement in creatinine and lipid profile, with significantly fewer cardiovascular events without differences in acute rejection or new-onset hyperglycemia incidences after conversion [52]. However, results from the same study after 5 years of follow-up do not demonstrated impact on patient or graft survival [53]; these follow-up findings are almost shared by other multicenter randomized trials with similar design [65][66][67][68]. Some critics in these studies remained over the fact that some irreversible fibrosis at enrollment time limited the possibility of showing a less toxic profile of tacrolimus; other explanations include a higher exposure to mycophenolic acid in tacrolimus group (an interaction between cyclosporine and mycophenolic acid reduces plasma levels of the latter) and cyclosporine through levels relatively higher in patients with dysfunction late after transplantation [62,[69][70][71][72][73].…”
Section: Switching To Another Calcineurin Inhibitormentioning
confidence: 79%